The Beijing Effect: China's "Digital Silk Road" as transnational data governance - Erie, MS; Streinz, T (New York University School of Law, 2021)
China shapes transnational data governance by supplying digital infrastructure to emerging markets. The prevailing explanation for this phenomenon is “digital authoritarianism” by which China exports not only its technology but also its values and governance system to host states. Contrary to the one-size-fits-all digital authoritarianism thesis, this Article theorizes a “Beijing Effect,” a combination of “push” and “pull” factors that explains China’s growing influence in data governance beyond its borders. Governments in emerging economies demand Chinese-built digital infrastructures and emulate China’s approach to data governance in pursuit of “data sovereignty” and digital development. China’s “Digital Silk Road,” a massive effort to build the physical components of digital infrastructure (e.g., fiber-optic cables, antennas, and data centers), to enhance the interoperability of digital ecosystems in such developing states materializes the Beijing Effect. Its main drivers are Chinese technology companies that increasingly provide telecommunication and e-commerce services across the globe. The Beijing Effect contrasts with the “Brussels Effect” whereby companies’ global operations gravitate towards the EU’s regulations. It also deviates from US efforts to shape global data governance through instruments of international economic law. Based on a study of normative documents and empirical fieldwork conducted in a key host state over a four-year period, we explain how the Beijing Effect works in practice and assess its impact on developing countries. We argue that “data sovereignty” is illusory as the Chinese party state retains varying degrees of control over Chinese enterprises that supply digital infrastructure and urge development of legal infrastructures commensurate with digital development strategies.